Emotion regulation difficulties and problematic mukbang watching: The mediating role of psychological distress and impulsivity - Kagan Kircaburun; Andrew Harris; Filipa Calado; Mark D. Griffiths (Psychiatry Research Communications, 2024)
There is accumulating evidence that mukbang (i.e., eating broadcasts) watching may be another emerging online behaviour that has the potential to become uncontrolled and harmful among a small number of individuals. However, there is still a large gap in the literature regarding the psychological and mental health predictors of problematic mukbang watching. Due to the paucity of research, the present study investigated the emotional and psychological correlates of problematic mukbang watching (PMW) including emotion regulation difficulties (ERDs), impulsivity facets (i.e., negative urgency, positive urgency, sensation seeking, lack of premeditation, lack of perseverance), and psychological distress (i.e., depression, anxiety, stress). A total of 513 adults (54% female; Mage = 32.05 years, SD = 11.14) who watched mukbang in the past seven days completed a survey including psychometric assessment tools for the aforementioned variables. ERDs were directly and indirectly related to PMW via anxiety and positive urgency. Daily time spent watching mukbang was also moderately positively associated with PMW. Consequently, the present study suggests that individuals with emotional and psychological impairments may use PMW as a maladaptive coping strategy.